2019
DOI: 10.3389/fpsyt.2019.00287
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tau Protein on the Antidepressant Effects of Ketamine in the Chronic Unpredictable Mild Stress Model

Abstract: Tau protein is known to play an important role in maintaining microtubule assembly and stabilization, and maintaining the normal morphology of neurons, but several studies have found that chronic stress leads to Tau hyperphosphorylation. A large number of clinical trials have found that ketamine, which is an N-methyl-D-aspartate receptor antagonist, produces a rapid, long-lasting, and potent antidepressant effect in patients suffering from major depression. This rapid antidepressant effect of ketamine, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 54 publications
2
15
1
Order By: Relevance
“…Another study reported that long‐term administration of ketamine in mice (30 mg/kg for 3 and 6 months) and monkeys (1 mg/kg for 6 months) induced tau hyperphosphorylation at S199, an epitope that was not affected by ketamine/xylazine in our experimental design. A recent study found that chronic unpredictable mild stress was accompanied by tau hyperphosphorylation at S396 and S404, and that ketamine was able to decrease this hyperphosphorylation of tau in the synapses of C57BL/6 mice, which differs from the higher phosphorylation we observed at S396 and S404 following ketamine/xylazine injection. It was also previously reported that the use of ketamine alone decreased CaMKII phosphorylation in the hippocampus and cortex of rats, which is the opposite of what we observed here when using ketamine in combination with xylazine.…”
Section: Discussioncontrasting
confidence: 87%
“…Another study reported that long‐term administration of ketamine in mice (30 mg/kg for 3 and 6 months) and monkeys (1 mg/kg for 6 months) induced tau hyperphosphorylation at S199, an epitope that was not affected by ketamine/xylazine in our experimental design. A recent study found that chronic unpredictable mild stress was accompanied by tau hyperphosphorylation at S396 and S404, and that ketamine was able to decrease this hyperphosphorylation of tau in the synapses of C57BL/6 mice, which differs from the higher phosphorylation we observed at S396 and S404 following ketamine/xylazine injection. It was also previously reported that the use of ketamine alone decreased CaMKII phosphorylation in the hippocampus and cortex of rats, which is the opposite of what we observed here when using ketamine in combination with xylazine.…”
Section: Discussioncontrasting
confidence: 87%
“…Since mice deficient in the serotonin neurotransmitter showed reduced depression-like behavior and chronic administration of the SSRI fluoxetine lead to increased hippocampal neurogenesis [77], this may be a feasible medication to restore neurogenesis in adults. In preclinical and clinical studies a single treatment of the antidepressant ketamine has been sufficient to relieve depressive symptoms in adult patients and C57BL/6 mice previously exposed to chronic stress [78,79]. In humans, ketamine is known to relief symptoms in a very short period of time, but more investigation is needed to ameliorate or prevent associated side effects [79].…”
Section: Discussionmentioning
confidence: 99%
“…Combined stress and TBI increased neuroinflammation, axonal injury and behavioral deficits [40]. CVS induces Tau phosphorylation at Ser396 and Ser404 [68]. Unpublished work by one of us (A.F.Z.)…”
Section: Repetitive Mild Traumatic Brain Injury (Rmtbi) Plus Stress Smentioning
confidence: 99%